Pure Essential Submodules - Ibrahim, Omar Hameed; Al-Mothafar, Nuhad Salim (Iraqi Journal of Science, 2025)
In this work, we generalized the notion of essential submodules by introduce the notion that namely pure essential submodules. We also introduce two notions pure relative complement submodules and pure uniform modules, as well as some other related concepts. The fundamental characteristics of these ideas are investigated.